Experimental study of the size-dependent photoluminescence emission of CBD-grown PbSe nanocrystals on glass. (5th May 2020) - Hemati, Tahere; Weng, Binbin
Abstract: In this work, we study the size-dependent properties of Photoluminescence (PL) emissions of PbSe Nanocrystals (NCs) grown by Chemical Bath Deposition (CBD) method. In previous studies, PL emissions have been tuned by CBD-grown PbSe, and the growth mechanism was dependent on crystalized substrates such as GaAs. In this research, however, PL emissions are controlled over the midinfrared (MIR) range, through PbSe NCs, which are deposited on glass as an amorphous material. This study proposes an alternative approach to control PL emissions, which provides us with more freedom to fabricate low-cost MIR light sources as crucial components in remote sensing and gas analysis. Moreover, in this study, the advantage of the post-thermal method to control the NCs size, compared to the growth temperature, is shown.